THE PEDAGOGUE AND PHYSICAL EDUCATION IN THE EARLY ELEMENTARY EDUCATION: CHALLENGES AND TRAINING OF LIMITATIONS - Souza Candido, Cicero Eduardo; Floro, Elisangela Ferreira [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2015)
This research is a study carried along by the nine pedagogy courses from the higher education, operating in the Triangulo do Crajubar region, which is a metropolitan zone located in the region of Cariri, in the state of Ceara, whose objective is to analyze the teacher's training process, since the legislation under the number 11.274/2009 has blamed the reference earlier grades elementary school teachers, usually a pedagogue for lecturing the Physical Education classes. Therefore, we set out to investigate in which ways the curriculum and the menus of the disciplines that refer to Physical Education allow teachers to plan, evaluate and develop physical education classes that encourage the earlier elementary school student's physical and cognitive development. It is a basic and qualitative research, whose analysis is based on surpassing critical theory. The collected data were organized into categories, through them is possible for us to notice that it was given much emphasis on recreation, rather than an extensive, cultural and a full-body experience.
Keywords: Educators; Physical Education; Professional Qualification